AAV-mediated delivery of osteoblast/osteoclast-regulating miRNAs for osteoporosis therapy - Aijaz Ahmad John; Jun Xie; Yeon-Suk Yang; Jung-Min Kim; Chujiao Lin; Hong Ma; Guangping Gao; Jae-Hyuck Shim (Elsevier, 2022)
Osteoporosis occurs due to a dysregulation in bone remodeling, a process requiring both bone-forming osteoblasts and bone-resorbing osteoclasts. Current leading osteoporosis therapies suppress osteoclast-mediated bone resorption but show limited therapeutic effects because osteoblast-mediated bone formation decreases concurrently. We developed a gene therapy strategy for osteoporosis that simultaneously promotes bone formation and suppresses bone resorption by targeting two microRNAs (miRNAs)-miR-214-3p and miR-34a-5p. We modulated the expression of these miRNAs using systemically delivered recombinant adeno-associated viral (rAAV) vectors targeting the bone. rAAV-mediated overexpression of miR-214-3p or inhibition of miR-34a-5p in the skeleton resulted in bone loss in adult mice, resembling osteoporotic bones. Conversely, rAAV-mediated inhibition of miR-214-3p or overexpression of miR-34a-5p reversed bone loss in mouse models for postmenopausal and senile osteoporosis by increasing osteoblast-mediated bone formation and decreasing osteoclast-mediated bone resorption. Notably, these mice did not show any apparent pathological phenotypes in non-skeletal tissues. Mechanistically, inhibiting miR-214-3p upregulated activating transcription factor 4 in osteoblasts and phatase and tensin homolog in osteoclasts, while overexpressing miR-34a-5p downregulated Notch1 in osteoblasts and TGF-β-induced factor homeobox 2 in osteoclasts. In summary, bone-targeting rAAV-mediated regulation of miR-214-3p or miR-34a-5p is a promising new approach to treat osteoporosis, while limiting adverse effects in non-skeletal tissues.